2018
DOI: 10.1371/journal.pone.0192973
|View full text |Cite
|
Sign up to set email alerts
|

Private healthcare provider experiences with social health insurance schemes: Findings from a qualitative study in Ghana and Kenya

Abstract: BackgroundIncorporating private healthcare providers into social health insurance schemes is an important means towards achieving universal health coverage in low and middle income countries. However, little research has been conducted about why private providers choose to participate in social health insurance systems in such contexts, or their experiences with these systems. We explored private providers’ perceptions of and experiences with participation in two different social health insurance schemes in Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 32 publications
10
56
0
Order By: Relevance
“…Furthermore, as a growing number of low and middle-income countries commit to achieving universal health coverage, one key challenge is how to extend coverage to the private sector [18]. The majority of Sub-Saharan African population access health care in private healthcare facilities [19]. Similarly, our study revealed that the majority of participants sought primary care in private healthcare settings and paid out-of-pocket for their health care.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Furthermore, as a growing number of low and middle-income countries commit to achieving universal health coverage, one key challenge is how to extend coverage to the private sector [18]. The majority of Sub-Saharan African population access health care in private healthcare facilities [19]. Similarly, our study revealed that the majority of participants sought primary care in private healthcare settings and paid out-of-pocket for their health care.…”
Section: Discussionmentioning
confidence: 65%
“…Eliminating the cost barrier will in the long term be cost effective for the Nigerian health system as it would have greater population benefit. Challenges stemming from NHIS-delayed reimbursements, cost recovery and low revenue for primary health care services are faced by private health providers [19]. Hence forprofit private health sector providers may be averse to offering comprehensive preventive care programs due to these problems.…”
Section: Discussionmentioning
confidence: 99%
“…Payment rates act as the starting point for negotiations between health care providers and purchasers . The reviewed literature suggests that health care providers preferred a PPM that had a higher payment rate compared to one whose rate was low on average . Sufficiency of payments to cover the cost of services was identified by health care providers in 4 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of timely payments to health care providers was a frequent characteristic mentioned in 3 of the selected papers . The utility of timeliness of payments was for budgeting purposes and smooth provision of services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation